Peranan Pendidikan Islam dalam Wawasan Parenting Berbasis Monitoring Psikologis Anak (Childrens’s Psychology) - Fannisa Hafidhia Suryana; Salsabila Fitri Pratami; Zilva Karimah Azahra; Mohammad Rindu Fajar Islamy (AR-RASYID : Jurnal Pendidikan Agama Islam, 2023)
This study contains a discussion of the role of Islamic education in parenting perspectives associated with the main domain of the stages of child development and their psychology. The rise of news about children's behavior that is not commendable and the behavior of children who tend to oppose parental advice is also caused by several crucial factors, especially for Muslims, one of which is the lack of application of Islamic religious education as a guide in raising children. If parents forbid it correctly, the child will also apply commendable behavior in his life, not only limited to behavior but can be embedded in the child's psychology both from the way children communicate, think, and also in making their own decisions (deciding for themselves). Researchers raise this issue with the aim of encouraging parents to be able to apply Islamic education in parenting and link it to the child's psychological stages, namely (a) social and emotional children, (b) children's language/communication, (c) children's movement/physical development , and (d) cognitive (learning, thinking, solving problems). While the research method used in this study is the method of interviewing through several trusted sources which is carried out through voice notes with the WhatsApp application, chat room, or telephone. Based on these interviews it was found that the scientific theories (child psychologically) presented by our sources are directly proportional to parenting taught by Islam.